Efficacy of Combination Docetaxel and Nintedanib in Advanced Non-Small Cell Lung Cancer in Thailand: A Multicenter Study - Korphaisarn, Krittiya; Danchaivijitr, Pongwut; Reungwetwattana, Thanyanan; Chewaskulyong, Busayamas; Thongthieang, Luangyot; Chindaprasirt, Jarin; Maneenil, Kunlatida; Sathitruangsak, Chirawadee; Vinayanuwattikun, Chanida (Frontiers in Oncology, 2021)
Introduction The mainstay systemic treatment for non-oncogenic addictive advanced stage non-small cell lung cancer is chemotherapy. Anti-angiogenic agents are additive compounds that enhance disease control and leads to improvement of overall survival benefit. Recently PD-(L)1 blockage, a checkpoint inhibitor, has been adopted as another line of treatment. Sequential strategy to enhance efficacy of combination docetaxel and nintedanib after immunotherapy, correlated with genomic mutation, has been explored. Method A retrospective cohort study of 56 patients from 8 centers in Thailand who received combination docetaxel and nintedanib via the Thai nintedanib Named Patient Use program was conducted. Demographic characteristics, treatment details and treatment responses were retrieved from medical records. Results The majority of patients were male (62.5%) with adenocarcinoma subtype (88%). Thirty-five percent had sensitizing EGFR mutation. Combination docetaxel and nintedanib was given as second to forth line of treatment. Median PFS of docetaxel/nintedanib was 5.6 months [95% CI 4.8-6.9]. Median OS of the entire cohort was 22.5 months [95% CI 20.2-31.1]. Among them, only 4 patients received this combination after immunotherapy which limited the validity of efficacy analysis. Median PFS of those 4 patients was 7.9 months [range 5.2-9.1] which was slightly higher than the remaining cohort (median PFS 4.5 months, 95% CI: 4.0-6.0, p-value 0.09). Among adenocarcinoma subtype, relapse-time of platinum-doublet chemotherapy of more than 6 months was solely indicated as a benefit of combination docetaxel/nintedanib treatment than relapse-time of platinum-doublet chemotherapy of less than 6 months by multivariate HR of PFS 0.32 [95% CI: 0.14-0.68, p-value 0.003]. Conclusion Combination docetaxel and nintedanib provided more benefit in relapse-time of platinum-doublet chemotherapy of more than 6 months in advanced stage adenocarcinoma lung cancer. Neither EGFR nor ALK alteration influenced the outcome of treatment.